RELEVANSI NILAI INFORMASI AKUNTANSI (BOOK VALUE DAN EPS) DAN UKURAN PERUSAHAAN BERDASARKAN NILAI KAPITALISASI PASAR: (Studi pada Perusahaan Terdaftar di Bursa Efek Indonesia) - Cyrillius Martono; Bernadetta Diana Nugraheni (STIE Mahardhika, 2023)
The purpose of this study is to examine the value relevance of accounting information (Book value and Earning Pershare) and firm size. The size of the company in this study is divided into large companies and small companies based on the market capitalization value. This research was conducted using the model portfolio-returns approach and regression approach. To test the value relevance of accounting information will be translated using a regression approach to stock prices, while to measure the value relevance of earnings per share and book value, the adjusted coefficient of determination (adj R2) is used to the company's stock price. Based on the results of this study, it shows that Book value and Earning Pershare have an influence on the company's stock price. Meanwhile, based on the adjusted coefficient of determination (adj R2) of earnings per share and book value, it shows a strong relationship to the company's stock price. The results of other studies based on company size show that book value and earning percentage in large-scale companies have an effect on the company's stock price. Based on the adjusted coefficient of determination (adj R2) value of Earning Pershare and book value, small-scale companies show a weak relationship strength, and large-scale companies show moderate strength of the relationship.